Chocolate milk as a post-exercise recovery aid - Karp, J. R.; Johnstone, J. D.; Tecklenburg, S.; Mickleborough, T. D.; Fly, A. D.; Stager, J. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2006)
Nine male, endurance-trained cyclists performed an interval workout followed by 4 h of recovery, and a subsequent endurance trial to exhaustion at 70% VO2max, on three separate days. Immediately following the first exercise bout and 2 h of recovery, subjects drank isovolumic amounts of chocolate milk, fluid replacement drink (FR), or carbohydrate replacement drink (CR), in a single-blind, randomized design. Carbohydrate content was equivalent for chocolate milk and CR. Time to exhaustion (TTE), average heart rate (HR), rating of perceived exertion (RPE), and total work (WT) for the endurance exercise were compared between trials. TTE and WT were significantly greater for chocolate milk and FR trials compared to CR trial. The results of this study suggest that chocolate milk is an effective recovery aid between two exhausting exercise bouts.